Gestational Weight Gain Video Module Improves Patient Knowledge of Weight Gain in Pregnancy [12D]. (May 2020) - Milone, Gina F.; Tiwari, Mahesh; McInerney, Hailey; Franz, Brynn; Potkin, Katya; Persad, Malini D.
Abstract : INTRODUCTION: Approximately 70% of pregnant women gain weight outside of the National Academy of Medicine's established guidelines for gestational weight gain (GWG) in pregnancy. We set out to determine if a GWG video module improves patient knowledge of GWG goals. METHODS: A prospective cohort study was performed from January 2019 through August 2019 with Institutional Review Board approval. Women were allocated to routine care versus a video arm after informed consent was obtained. Both arms completed a baseline GWG knowledge questionnaire. Those undergoing routine care received provider counseling. Those in the video arm underwent routine counseling and viewed a 5-minute video module based on the American College of Obstetricians and Gynecologists and National Academy of Medicine approved material on body mass index (BMI) specific GWG goals. The GWG knowledge questionnaire was repeated in 4 weeks. Maternal demographics and baseline characteristics were collected from the electronic medical record. Independent sample t-tests, chi square analyses and Fisher exact tests were used to compare arms, with a P <.05 deemed statistically significant. RESULTS: A total of 52 women were included in the study, 26 in the routine counseling arm and 26 in the video module arm. Maternal demographics and baseline characteristics including BMI were similar between groups. Compared to routine counseling, women in the video module arm had a statistically significant increase in GWG knowledge (10.0±2.0 versus 12.5±2.3, P <.001). CONCLUSION: Compared to routine provider counseling, a GWG video module significantly improves patients' knowledge of GWG goals. Utilization of a GWG video enhances provider counseling.